Sliding Mode Active Disturbance Rejection Control for Magnetorheological Impact Buffer System - Wang, Bin; Wang, Wanjun; Li, Zhaochun (Frontiers in Materials, 2021)
In the magnetorheological (MR)impact buffer system, the internal or external disturbance of MR damper is one of the main reasons that affect the buffer performance of the system. This study aims to suppress or eliminate the influence of the disturbance of the MR damper. The continuous terminal sliding mode control (CTSMC) strategy with a high gain has strong anti-disturbance ability. However, the high gain may cause the fluctuation of the damping force of the system. Therefore, a composite control strategy of sliding mode active disturbance rejection control (ADRC) based on extended state observer (ESO) is proposed in this paper. The total disturbance of the system is estimated by ESO in real time, and the estimated disturbance is used as a feedforward compensation to the controller to reduce the influence of disturbance on the system. And the gain of the CTSMC law of the closed-loop system can be reduced. In addition, Lyapunov stability criterion is used to ensure the stability of the proposed controller. In order to verify the performance of the proposed CTSMC controller on response speed, overshoot and hysteresis suppression ability, the window function, square wave function and multistep function are given as the inputs of the control system. To verify the performance of the proposed sliding mode ADRC for the MR impact buffer system, the mechanical model and the control model are established and simulated by MATLAB/Simulink. The simulation results show that the CTSMC controller has the fastest response time, no overshoot and can suppress the hysteresis nonlinearity of the MR device compared with open-loop control, PID control and fractional order PID control. The MR impact buffer system with the sliding mode ADRC obtained the minimum peak value of 4350N within the permitted buffer displacement range compared the other three traditional control methods. That means the proposed control method in this paper has advantage on buffer performance for the MR impact buffer system.